A Systematic Investigation of Research Trends of ELT and EFL Found in JEES and JEFL Journals - Amaliawati, Shafira; Aulia, Nila; Susanti, Ani (Universitas Muhammadiyah Gresik, 2024)
Global demand for English as a foreign language (EFL) has generated a demand for learning options that maintain students motivated to study the language. The purpose of this study is to analyze ELT and EFL trends using published JEES and JEFL publications as a basis. The period under examination was from 2019 to 2023. Researchers investigated the 229 studies that were published in journals throughout this time period, concentrating on providing an overview of the methodology, subjects, and data collection techniques of the populations that were studied. In order to address the emerging topics in contemporary EFL and ELT research, we have also attempted to provide a summary of the literature's major findings. Thus, this work provides a thorough synthesis and analysis of current research trends in EFL and ELT in Indonesia. Furthermore, most of the studies featured university students and adults as well as teachers from general education. The results of this study show that the most discussed topics in both journals are about teaching practices and methods. The researcher also found extensive use of multimedia and ICT, through which we can identify a viable path for enhancing language learning, teaching, and future research. This review highlights the need for sustainable interventions and studies with diverse populations in the expanding field of EFL.